Availability of anticancer medicines in public and private sectors, and their affordability by low, middle and high-income class patients in Pakistan - Muhammad Rehan Sarwar; Sadia Iftikhar; Anum Saqib (BMC Cancer, 2018)
Abstract Background Availability and affordability of anticancer medicines is a matter of great concern especially for low and middle income countries e.g., Pakistan. Prime focus of this study was to evaluate the availability of anticancer medicines in public and private sectors, and their affordability among patients with different income levels. Methods A descriptive, cross-sectional survey was conducted in 22 cancer care hospitals (18 public hospitals and 04 private hospitals) and 44 private pharmacies in Punjab, Pakistan. All (n = 4400) participants were ≥18 years of age. Data were collected at different intervals and analyzed by using Statistical Packages for Social Sciences (IBM SPSS Statistics for Windows, Version 21.0. Armonk, NY: IBM Corp.) Results A total of 4913 patients were approached, and 4400 responded to the survey (response rate = 89.6%). Non-hodgkin lymphoma (12.3%), breast cancer (8.6%), and leukemia (7.6%) were the most prevailing cancers. Conventional medicines like cisplatin, cyclophosphamide, and etoposide were the most prescribed medicines. Oncologists were reluctant to prescribe newer anticancer medicines due to high prices. Originator brands (OBs) were more readily available (52.5%) but less affordable (53.4%); whereas, lowest price generics (LPGs) were less available (28.1%) but more affordable (67.9%). Anticancer medicines were more affordable by the high income class patients than the low income class patients. Conclusion The availability of both OBs and LPGs was greater at private hospitals and pharmacies as compared to public hospitals. The high income class had more affordability of both OBs and LPGs; however, LPGs were more affordable for all income classes.